The investigation of pro-oxidant: Effect of a new Schiff base and its metal complexes (Cu, Ni, Co, Zn, Mn) - Yildirim, Işil; Karatepe, Mustafa (Free Radicals and Antioxidants)
Background: Multifarious biological activities of Schiff base (SB) derivatives are well-known. Aim: In this study aimed that investigation of pro-oxidant effect of ([(2-hydroxybenzylidene)-3methylurea]) derivative SB and its metal complexes. Material and Methods: Pro-oxidant effect was determined by antioxidant vitamins levels effect against malonyldialdehyde (MDA), which is an indicator of lipid peroxidation in the serum of rats. To this end; 4-6 weekly Wistar albino rats were injected 25 mg/L 2 weeks subcutaneously for 3 days apart by 1 ml injection of a new compound and were then sacrificed 16 days later. Effect of these compounds serum MDA concentration, which is an indicator of lipid peroxidation, serum antioxidant vitamins A, E, C levels were measured with high-performance liquid chromatograph. In the comparison done among a group. Result: It was observed that although other serum parameters were altered, groups in comparison with each other in the MDA, vitamins A, E and C concentrations were not statistically changed. Conclusion: It may conclude that the compounds tested the administered dose does not cause oxidative stress.
Keywords: high-performance liquid chromatograph; malonyldialdehyde; Schiff base; Antioxidant vitamins (A E C)